2021
DOI: 10.1038/s41420-021-00611-z
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA-15a from mesenchymal stem cells impedes hepatocellular carcinoma progression via downregulation of SALL4

Abstract: Hepatocellular carcinoma (HCC) is a heterogeneous tumor with an increased incidence worldwide accompanied by high mortality and dismal prognosis. Emerging evidence indicates that mesenchymal stem cells (MSCs)-derived exosomes possess protective effects against various human diseases by transporting microRNAs (miRNAs or miRs). We aimed to explore the role of exosomal miR-15a derived from MSCs and its related mechanisms in HCC. Exosomes were isolated from transduced MSCs and co-incubated with Hep3B and Huh7 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…SALL4 regulates HCC progression by interacting with miRNAs. miR-15a inhibited cell proliferation, migration, and invasion in HCC by downregulating SALL4 [142]. Furthermore, miR-497 directly targeted SALL4 to inhibit SALL4 expression and the self-renewal and metastasis of HCC [91].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…SALL4 regulates HCC progression by interacting with miRNAs. miR-15a inhibited cell proliferation, migration, and invasion in HCC by downregulating SALL4 [142]. Furthermore, miR-497 directly targeted SALL4 to inhibit SALL4 expression and the self-renewal and metastasis of HCC [91].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…These missense variants maybe increase protein stability, with posttranslational regulation, suggesting the essential genetic involvement of SALL4 in the etiology of POI. However, caution must be taken, since SALL4 is known to function as an oncogene in various death-related tumors [20,134,142,152].…”
Section: Ovarian-related Diseasesmentioning
confidence: 99%
“…Plenty of studies have reported the association of exosomal lncRNAs with HCC. For instance, Ma et al 62 have proposed a mechanism in which exosomes derived from mesenchymal stem cells can transfer miR‐15a to HCC cells to inhibit the cellular proliferation, migration and invasion by negatively regulating SALL4.…”
Section: Introductionmentioning
confidence: 99%
“…OS was computed in months from the date of diagnosis to the time of death, regardless of cause, and DFS was defined as the time from surgery to the first event of either disease recurrence or death due to any cause. 21 …”
Section: Methodsmentioning
confidence: 99%